Growth optimization of N-fixer, isolated from biofertilizer - Intan Noorleana, Rosdi (2009)
The objectives of this experiment were to obtain the optimum temperature, pH and the requirement of carbon sources needed for the growth of N-Fixer bacteria. This research can be divided into two parts which are the standard curve preparation followed by optimization of the experiments. Three standard curves needs to be constructed; growth, glucose and CFU curves. These three curves will be used in optimizing the growth condition of N-fixer. Set of experimental works were designed by DOE software using full factorial function. Based on the experiment results, it shows that the optimum pH and temperature for the growth of N-Fixer is at pH 6 and 30°C respectively. As for the requirement of carbon sources, 10 g/L was applicable to avoid the surplus glucose become toxic to microorganisms. As the conclusion, the concentration of glucose plays a major role in the fermentation process (18 hours) either to increase the number of N-fixer cell or to decrease it. Therefore, by maintaining it at 10g/L the number of cell can achieve the upper limit to where it can be produced which is about 1.6834E8 cell/mL .